Analisis Jenis Vegetasi Strata Tiang di Bukit Sulap Kota Lubuklinggau - Merti Triyanti; Destien Atmi Arisandy (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2019)
The purpose of this study was to determine the diversity of stratum vegetation in Sulap City, Lubuklinggau City based on composition, density of vegetation types and to know abiotic factors for stratum vegetation in Sulap Hill, Lubuklinggau City. This type of research is quantitative descriptive. The method used is the distance method (Centered Quarter Point). The population in this study were all species of stratum vegetation in the Bukit Sulap vegetation in Lubuklinggau City. The analysis used is in the form of density, frequency, dominance, important value index, and diversity index. The results of the study, obtained data in the study area A found 16 species of pole strata. In the study area B, 14 species of stratum were obtained, whereas in the study area C, 24 species of stratum were found. Measured abiotic factors are the air temperature in the Sulap Hill of Lubuklinggau City ranging from 28.30C - 300C with air humidity of 86% - 93%. Soil moisture ranges from 8-17 while the acidity (pH) of the soil ranges from 6.3 to 6.7. Conclusion, the mean of the Important Value Index (INP) in the Pole strata in the areas of study A, B, and C respectively is ketapang, starfruit, and coffee. Keywords: analysis, vegetation, pole strata, magic hill